Enhancing the sustainability of chemical vapour polishing of additive manufactured ABS parts using a vacuum chamber. Issue 6 (17th October 2017) - Pietanza, Sergio; Sorgente, Donato; Percoco, Gianluca
Abstract : Purpose: In this paper, the authors propose an experimental set-up to study the chemical vapour polishing technique confining pure dimethylketone atmosphere at a fixed temperature in a vacuum chamber. The purpose of this paper is to improve conventional vapour treatments lowering the amount of solvent, lowering time and temperature needed and improving the environmental impact of the technique. Design/methodology/approach: A factorial design of experiments is adopted to understand the effect of the treatment on roughness and on the surface morphology of treated specimens. Findings: The proposed method improves several aspects of well-known methods based on water–dimethylketone liquid solution such as: no interaction between water and workpiece and higher capability of process management. It also improves several aspects of well-known methods based on vapour, lowering the amount of solvent, time and temperature compared to conventional vapour treatments. Originality/value: Chemical vapour polishing is a well-known technique for smoothing additive manufactured acrylonitrile butadiene styrene (ABS) parts. Several data and users' experiences are available on the Web about this topic. In recent scientific literature, a few papers are available about this topic, dealing with how process parameters affect the final surface roughness. In the present paper, the authors propose to improve the process performing the process using dimethylketone into a vacuum chamber. The main advantages are the significant reduction of the solvent needed to perform the process and lower time needed to obtain same results as atmospheric pressure treatments.